Development of a novel energy efficient phase change emulsion for air conditioning systems - Shao, Jingjing (2015)
Buildings represent more than 40% of final global energy consumption, among which 50%-60% of energy consumption is attributed to Heating, Ventilation and Air Conditioning (HVAC) systems. The application of phase change material emulsions (PCMEs) in air conditioning systems is considered to be a potential way of saving energy because with their relatively higher energy storage capacity, they are able to reduce flow rate whilst delivering the same amount of cooling energy. PCMEs can also simultaneously act as cold energy storage to shift peak-load to off-peak time and improve coefficient of performance of systems. However, one of the main barriers affecting the application of PCME is the difficulty in maintaining stability in the emulsions without experiencing any temperature stratification during phase change process.